Reimagining Community Education with First Responders: Lessons from a University–Fire Department Partnership - Edith Gnanadass; Wendy Griswold; Kevin Spratlin; Amanda Bowen (Adult Education Research Conference, 2025)
Drawing on a partnership between a university and a city fire department, this session will discuss the opportunities and challenges of doing community education with first responders.
Keywords: community education; adult learning and first responders; trauma-informed learning